2021
DOI: 10.1007/s10265-021-01296-2
|View full text |Cite
|
Sign up to set email alerts
|

Rich but not poor conditions determine sex‐specific differences in growth rate of juvenile dioecious plants

Abstract: Causes of secondary sexual dimorphism (SSD) in dioecious plants are very poorly understood, especially in woody plants. SSD is shown mainly in mature plants, but little is known about whether secondary sexual dimorphism can occur in juveniles. It is also assumed that stress conditions intensify differences between the sexes due to the uneven reproductive effort. Therefore, the following research hypotheses were tested: (1) secondary sexual dimorphism will be visible in juveniles; (2) unfavourable soil conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This suggests that, although in a rich environment, female plants invest more into production of numerous flowers, while the efficiency of seed development and seed production is related to factors other than just nutritional availability and pollen availability [ 47 ]. Moreover, our earlier studies showed that fertilised female plants of both species are characterised by higher photosynthetic activity [ 38 , 48 ] and higher biomass [ 39 ] than their non-fertilised counterparts. These observations indicate that the allocation of plant resources to seed production is a reasonable/controlled investment of resource allocation; thus, in a non-fertilised environment, when the plant has already invested part of the available resource for female reproductive structure development, the necessary resources were provided by the plant (at the cost of vegetative growth or resource allocation) to ensure development of seeds [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that, although in a rich environment, female plants invest more into production of numerous flowers, while the efficiency of seed development and seed production is related to factors other than just nutritional availability and pollen availability [ 47 ]. Moreover, our earlier studies showed that fertilised female plants of both species are characterised by higher photosynthetic activity [ 38 , 48 ] and higher biomass [ 39 ] than their non-fertilised counterparts. These observations indicate that the allocation of plant resources to seed production is a reasonable/controlled investment of resource allocation; thus, in a non-fertilised environment, when the plant has already invested part of the available resource for female reproductive structure development, the necessary resources were provided by the plant (at the cost of vegetative growth or resource allocation) to ensure development of seeds [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…T. baccata plants produce seeds within a one-year cycle with the base of the strobila developing in the autumn of the previous year, whereas in J. communis the seed-producing cycle lasts up to three years [ 35 , 37 ]. These species are characterised by gender-related ecological differences between the sexes within species [ 38 , 39 , 40 , 41 , 42 ], and population decline [ 37 , 43 , 44 ]. Thus, female plants of both species allocate resources for growth, defence, and seeds, but not pollen production, and can be great models to test the impact of long-term different nutritional availability on the female reproductive responses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, females were more dependent on adequate soil water for P acquisition. In humid (favourable) conditions, female individuals had higher sex‐related costs associated with greater nutrient requirements compared to males (Hultine et al, 2016; Nowak et al, 2021; Xia, He, Yu, Lv, et al, 2020). By contrast, in dry (unfavourable) conditions, males and females did not differ in leaf mineral nutrients (Dawson & Ehleringer, 1993).…”
Section: Discussionmentioning
confidence: 99%